Capsicum chinensis L. growth and nutraceutical properties are enhanced by biostimulants in a long-term period: chemical and metabolomic approaches - Ertani, Andrea; Pizzeghello, Diego; Francioso, Ornella; Sambo, Paolo; Sanchez-Cortes, Santiago; Nardi, Serenella (Frontiers in Plant Science, 2014)
Two biostimulants, one derived from alfalfa plants (AH) and the other obtained from red grape (RG), were chemically characterised using enzyme linked immuno-sorbent assays, Fourier transform infrared (FTIR) and Raman spectroscopies. Two doses (50 and 100 mL L-1 for RG, and 25 and 50 mL L-1 for AH) of biostimulants were applied to Capsicum chinensis L. plants cultivated in pots inside a tunnel. The experimental design consisted of the factorial combination of treatment (no biostimulant, plus AH, plus RG) at three doses (zero, low and high) and two time-course applications (at the second and fourth week after transplantation) and the effects were recorded at flowering and maturity. Both biostimulants contained different amounts of indoleacetic acid and isopentenyladenosine; the AH spectra exhibited amino acid functional groups in the peptidic structure, while the RG spectra showed the presence of polyphenols, such as resveratrol. These results revealed that at flowering, RG and AH increased the weights of fresh leaves and fruits and the number of green fruits, whereas at maturity, the biostimulants most affected the fresh weight and number of red fruits. At flowering, the leaves of the treated plants contained high amounts of epicatechin, ascorbic acid, quercetin and dihydrocapsaicin. At maturity, the leaves of the treated plants exhibited elevated amounts of fructose, glucose, chlorogenic and ferulic acids. Moreover, green fruits exhibited a high content of chlorogenic acid, p-hydroxybenzoic acid, p-coumaric acid and antioxidant activity, while both AH- and RG-treated red fruits were highly endowed in capsaicin. The 1H high-resolution magic-angle spinning (HRMAS)-nuclear magnetic resonance (NMR) spectra of red fruits revealed that both products induced a high amount of NADP+, whereas RG also increased glucose, fumarate, ascorbate, thymidine and high molecular weight species. Our results suggested that AH and RG promoted plant growth and the production of secondary me